Thyroid Function and Left Ventricular Structure and Function in the Framingham Heart Study - Pearce, Elizabeth N. (Mary Ann Liebert, Inc., 2010)
BACKGROUND: Thyroid hormone acts on the heart and peripheral vasculature in multiple ways. Even in patients with subclinical hypo- or hyperthyroidism, subclinical alterations in left ventricular (LV) structure and function may be associated with important clinical effects. Our objective was to determine whether thyroid function is related to echocardiographic indices of LV structure and function. METHODS: Cross-sectional association of serum thyroid-stimulating hormone (TSH) with two-dimensional-guided M-mode echo LV dimensions and function. Participants were 1376 Framingham Heart Study participants (61% women, mean age 69 years) who attended a routine examination 1979–1981. We excluded participants with myocardial infarction or heart failure, renal insufficiency, and missing data, and those using thyroid hormone or antithyroid medications. Serum TSH was measured 1977–1979. The following echocardiographic measurements were analyzed both as continuous variables and dichotomized at the top quintile: LV end-diastolic dimensions, LV wall thickness, LV mass, LV fractional shortening (an indicator of systolic function), and left atrial diameter. Sex-specific multiple regression models were adjusted for age, height, weight, blood pressure, heart rate, total to high-density lipoprotein cholesterol ratio, and the presence of diabetes, hypertension treatment, and valve disease. RESULTS: In multivariable linear models, log-TSH was not related to LV mass, LV wall thickness, or left atrial size in either sex, or to LV systolic function in men. Log-TSH had a borderline inverse association with fractional shortening (p = 0.06) in women. In multivariable logistic models, women with TSH <0.5 mU/L (n = 81) had a greater odds of being in the highest quintile of fractional shortening compared to euthyroid subjects (odds ratio 2.2, 95% confidence interval 1.3–3.8, p = 0.01). CONCLUSIONS: In our moderate-sized community-based sample, TSH concentration was not associated with LV structure in either sex, but was inversely related to LV contractility, consistent with the known inotropic effects of thyroid hormone.